2022
DOI: 10.1039/d2cc03474c
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic stannylation of white phosphorus

Abstract: Organophosphorus compounds (OPCs) are highly important chemicals, finding numerous applications in both academia and industry. Herein we describe a simple photocatalytic method for the stannylation of white phosphorus (P4) using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…The industrial and academic applications of these isolated products include flame retardants ( 5 and 10 ), [1b,18] Wittig reagents ( 7 ), and chemical precursors ( 9 ), [1b,19] among others. Significantly, the formation of 7 and 8 could be performed in the absence of base which contrasts with previous results where a base was necessary for functionalisation of the intermediate P−H bonds present in (Bu 3 Sn) x PH 3− x ( x =1 or 2), thus highlighting an additional advantage of instead proceeding via (Bu 3 Sn) 3 P only [5f] …”
Section: Methodscontrasting
confidence: 77%
See 3 more Smart Citations
“…The industrial and academic applications of these isolated products include flame retardants ( 5 and 10 ), [1b,18] Wittig reagents ( 7 ), and chemical precursors ( 9 ), [1b,19] among others. Significantly, the formation of 7 and 8 could be performed in the absence of base which contrasts with previous results where a base was necessary for functionalisation of the intermediate P−H bonds present in (Bu 3 Sn) x PH 3− x ( x =1 or 2), thus highlighting an additional advantage of instead proceeding via (Bu 3 Sn) 3 P only [5f] …”
Section: Methodscontrasting
confidence: 77%
“…It was possible to isolate product 4 from this one‐step reaction in excellent yield (86 %, see Scheme 3a and Section 2.2 in the Supporting Information). More significantly, it was confirmed that (Bu 3 Sn) 3 P ( 4 ) could also serve as an intermediate “P 3− ” synthon and be functionalised with suitable electrophiles in a similar fashion to the previous (Bu 3 Sn) x PH 3− x mixture [5f] . For example, treatment of crude (Bu 3 Sn) 3 P generated from P red directly with paraformaldehyde in ethanol followed by quenching with HCl furnished THPC ( 5 ) in excellent isolated yield (85 %, see Scheme 3b and Section 3.1 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 55%
See 2 more Smart Citations
“…The most common route involves the use of Cl 2 , through the highly toxic compound PCl 3 , which then reacts with corresponding nucleophilic reagents while releasing large amounts of hydrochloric acid, with much environmental contamination. 2 In recent years, several methods involving direct activation of white phosphorus for producing organophosphorus compounds have been gradually developed, including those involving (1) the formation of arylated phosphines (Ar 3 P) and related phosphonium salts (Ar 4 P + ), [3][4][5][6] (2) construction of novel complex organophosphorus compounds by obtaining stable aryl P 4 anion structures under the action of Lewis bases and acids, 7,8 (3) activation of P 4 with bilithium reagents to prepare phosphorylated cyclopentadienyl lithium salts and phosphorus-containing cyclic organometallic compounds, [9][10][11] etc. Owing to the potential dangers of direct conversions of P 4 to P 1 products, there is a strong desire to discover more environmentally friendly and safer inorganic phosphorus sources for the synthesis of various OPCs.…”
Section: Introductionmentioning
confidence: 99%